Development and Validation of Interactive Teaching Materials Based on Universal Design for Learning for Digital Marketing Learning at the Open University - Kadarisman Kadarisman; Romi Siswanto; Rhini Patmasari; Sucipto Sucipto; Fitra Jaya (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
The research aimed to develop and validate an interactive learning module effectively applicable in distance education. Using an Educational Research and Development (R&D) model with a mixed-methods approach, the study collected quantitative and qualitative data. Quantitative data were obtained from pre-tests and post-tests to measure cognitive improvement, analyzed using descriptive and inferential statistics (paired t-test or Wilcoxon test) and effect size calculation. Learning analytics from the LMS—such as clicks, video-watching duration, and quiz scores—supported the analysis. Qualitative data were gathered through semi-structured interviews, participant observation, and thematic analysis by Braun and Clarke, complemented with Likert-scale questionnaires, observation rubrics, and LMS logs. The findings revealed a significant improvement in students’ cognitive performance, with post-test scores (M = 13.24, SD = 1.07) much higher than pre-test scores (M = 3.67, SD = 1.41), t(19) = 25.43, p < 0.001, Cohen’s d = 5.69. LMS analytics showed high engagement, with 82% average video completion and frequent quiz participation. Over 85% of students reported greater satisfaction and motivation using the interactive module. The integration of short videos, diagnostic quizzes, and web simulations proved effective for self-directed learning and comprehension, supporting the Universal Design for Learning (UDL) framework in inclusive digital education.